2016
DOI: 10.1186/s12917-016-0725-5
|View full text |Cite
|
Sign up to set email alerts
|

Porcine epidemic diarrhea virus (PEDV) detection and antibody response in commercial growing pigs

Abstract: BackgroundLongitudinal samples from two production sites were used to (1) describe the pattern of PEDV shedding (rRT-PCR) in individual rectal swabs, pen fecal samples, and pen oral fluids (OF); (2) describe the kinetics of PEDV antibody by ELISA (IgA, IgG) testing of pig serum and pen oral fluid samples; and (3) establish cutoffs and performance estimates for PEDV WV ELISAs (IgA, IgG). Site One was PEDV positive; Site Two was PEDV negative. On Site One, pen samples (feces and oral fluids) and pig samples (rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 13 publications
6
68
0
5
Order By: Relevance
“…At the moment, very limited data have been published on the PEDV viral load during an outbreak under field conditions (Bjustrom-Kraft et al, 2016). The qPCR assay used in this study was validated according to the minimum information for quantitative real-time PCR experiments guidelines (Bustin et al, 2009; Table 3 ; Supplementary Table 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the moment, very limited data have been published on the PEDV viral load during an outbreak under field conditions (Bjustrom-Kraft et al, 2016). The qPCR assay used in this study was validated according to the minimum information for quantitative real-time PCR experiments guidelines (Bustin et al, 2009; Table 3 ; Supplementary Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…At the moment, very limited data have been published on the PEDV viral load during an outbreak under field conditions (Bjustrom-Kraft et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Due to low success rate of PDCoV VI in cell culture, currently PDCoV VI is not a reliable assay to determine whether infectious virus is present in a clinical specimen or if 'X' treatment will inactivate the virus. For PEDV, swine bioassay has been commonly used to assess infectivity of PEDV present in various samples, including feed and feed ingredients after disinfectant or other treatments (Bowman et al, 2015b;Dee et al, 2014b;Dee et al, 2015). Notably, some samples were PEDV VI negative after treatment but swine bioassay positive (Dee et al, 2015), emphasizing the importance and necessity of performing swine bioassay to reliably determine virus infectivity of a sample.…”
Section: Swine Bioassaymentioning
confidence: 99%
“…IgG, IgA, and IgM) in various specimen types. For example, PEDV ELISAs have been used to detect IgG and/or IgA antibodies in serum, oral fluid, and feces samples (Bjustrom-Kraft et al, 2016;Gerber et al, 2014;Gerber and Opriessnig, 2015). No publications have described dynamics of PDCoV antibody production and antibody duration as measured by PDCoV ELISAs.…”
Section: Enzyme Linked Immunosorbent Assays (Elisas)mentioning
confidence: 99%
“…Analysis of the PEDV serum IgG WV ELISA data showed that a S/P cutoff of ! 0.40 provided a diagnostic sensitivity of 0.99 (95% CI: 0.96, 1.00) and specificity of 0.98 (95% CI: 0.97, 0.99) (Bjustrom-Kraft et al, 2016). No cutoffs have been established for mammary secretion samples.…”
Section: Pedv Whole Virus Antibody Elisamentioning
confidence: 99%